2021
DOI: 10.1186/s40659-021-00360-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of vulpinic acid as a natural compound in the regulation of breast cancer-associated miRNAs

Abstract: Background Breast cancer is the most frequently diagnosed cancer, and no effective treatment solution has yet been found. The number of studies based on the research of novel natural compounds in the treatment of breast cancer has been increasing in recent years. The anticancer properties of natural compounds are related to the regulation of microRNA (miRNA) expression. Therefore, changing the profile of miRNAs with the use of natural products is very important in cancer treatment. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The results showed that VA significantly inhibited cell viability and induced apoptosis of human breast cancer cells while While it has no significant cytotoxic or apoptotic effects on non-cancerous cells [14]. Cansaran-Duman et al ( 2021) investigated the role of vulpinic acid (VA) on the progression of breast cancer and reported that VA could downregulate the expression of 12 miRNAs by silencing the FOXO-3 gene [20]. Another study reported that VA exhibited anti-cancer activity in the breast cancer cell lines MCF-7 and MDA-MB-453 by inhibiting Thioredoxin reductases-1 (TRXR1) enzyme, which is recognized as a cancer marker, preventing migration and inducing apoptosis [11].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that VA significantly inhibited cell viability and induced apoptosis of human breast cancer cells while While it has no significant cytotoxic or apoptotic effects on non-cancerous cells [14]. Cansaran-Duman et al ( 2021) investigated the role of vulpinic acid (VA) on the progression of breast cancer and reported that VA could downregulate the expression of 12 miRNAs by silencing the FOXO-3 gene [20]. Another study reported that VA exhibited anti-cancer activity in the breast cancer cell lines MCF-7 and MDA-MB-453 by inhibiting Thioredoxin reductases-1 (TRXR1) enzyme, which is recognized as a cancer marker, preventing migration and inducing apoptosis [11].…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies, vulpinic acid has been used for breast treatment as it induces apoptosis and suppresses Bcl-2 [ 152 ]. Cansaran-Duman et al [ 28 ] conducted an in vitro study and investigated the role of vulpinic acid on BC by regulating the expression of miRNA levels. They found that vulpinic acid induced apoptosis in MCF-7 by elevating the level of FOXO-3 and Bax, and suppressing Bcl-2 and pro-caspase-3,9, thus altering the tumor suppressor miRNAs (see Table 1 ).…”
Section: Recent Discoveries and Developments Of Natural Products Agai...mentioning
confidence: 99%
“…Recently, various natural products have been discovered and tested as anti-BC agents. These natural products are viridiflorol, verminoside, novel phloroglucinol derivatives, genistein, vulpinic acid, calcitrinone A, kaempferol, protopanaxadiol, thymoquinone, arctigenin, glycyrrhizin, 25-OCH3-PPD, oridonin, apigenin, wogonin, fisetin, curcumin, berberine, cimigenoside, and resveratrol [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. These natural products are alkaloids, antioxidants, phenolic compounds, flavonoids, and polyphenols in nature, and are obtained from herbal products and vegetables.…”
Section: Introductionmentioning
confidence: 99%